Social Values in the Novel Series Kami (Bukan) by J.S. Khairen and its Feasibility as Teaching Materials for Literature in High School - Hikmah, Mamluatul; Nuryatin, Agus; Haryadi Haryadi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the social values and suitability of the novel series Kami (Bukan) by J.S. Khairen, which contains four novel titles, including Kami (Bukan) Sarjana Kertas, Kami (Bukan) Jongos Berdasi, Kami (Bukan) Generasi Bac*t, and Kami (Bukan) Fakir Asmara for literature teaching materials in high school seen based on the content of social values. The approach in this research is the pragmatic approach. The research method used is the qualitative descriptive method. The research instrument used is a data card. The data collection techniques used are heuristic reading techniques and note-taking techniques. The data analysis technique in this research uses hermeneutic reading. The results of this study show that there are 178 data containing social values in the Kami (Bukan) novel series; each novel contains 54 data in the KBSK novel, 49 data in the KBJB novel, 28 data in the KBGB novel, and 47 data in the KBFA novel. The social values include 15 data on the value of devotion, 10 data on the value of helping, 10 data on the value of kinship, 3 data on the value of loyalty, 21 data on the value of caring, 3 data on the value of belonging, 4 data on the value of discipline, 13 data on the value of empathy, 4 data on the value of justice, 3 data on the value of tolerance, 9 data on the value of cooperation, 2 data on the value of democracy, 10 data on material values, 6 data on vital values, 22 data on spiritual values, 20 data on the value of the relationship between humans and fellow humans, 4 data on the value of the relationship between humans and nature, and 19 data on the value of the relationship between humans and themselves. The four novels are based on the criteria for the feasibility of teaching materials, which include aspects of language, psychology, cultural background, aesthetics, pedagogy, and suitability for learning objectives. Based on the study results, the novel series Kami (Bukan) by J.S. Khairen can be utilized as literature teaching materials in high school.